ROLE OF PROBIOTICS IN TYPE 2 DIABETES MELLITUS PATIENTS WITH HYPERTENSION: A REVIEW - Ni Made Suastini; Iwan Saka Nugraha; Made Dwike Swari Santi (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2023)
Background: Type 2 Diabetes Mellitus (DM) is one of a global health problem. One of the comorbidities that often occurs in patients with type 2 DM is hypertension. Hypertension can increase the risk of cardiovascular complications. One of the causes of type 2 DM and hypertension is gut dysbiosis. An imbalance of gastrointestinal microbiota contributes to chronic inflammation and effects on the insulin action, increases insulin resistance, and leads to endothelial dysfunction. The role of this inflammatory mediator is a new therapeutic target in type 2 DM patients with hypertension. Objective: to describe how probiotic effect in type 2 diabetic patients with hypertension. Methods: All articles were obtained by conducting an electronic search through Pubmed and Google Scholar. Results: Probiotics help to restore the balance of the gastrointestinal microbiota, produce anti-inflammatory mediators, and suppress the pro-inflammatory mediators to control the glycemic profile and blood pressure of patients with type 2 DM with hypertension. All the clinical trial showed that probiotic help to maintaining clinical outcome in diabetic patients with hypertension. Conclusion: Probiotic effective for glycemic control and blood pressure in type 2 DM with hypertension. Keywords: Diabetes; Hypertension; Gut dysbiosis; Probiotics; Inflammation mediators